Concerns about rising prices may raise prices - Steffen Huck; Hans-Theo Normann; Fidel Petros (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2024)
We use a laboratory experiment to investigate whether statements from a governmental institution expressing concerns about price increases trigger such increases by facilitating tacit collusion. Such statements on market conduct are disclosed after an exogenous and unexpected upward cost shock. The two potential channels affecting tacit collusion work through (i) a reduction of strategic uncertainty and (ii) an inducement of correlated beliefs. We find that issued statements of concern become a self-fulfilling prophecy, triggering price increases, and that a reduction in strategic uncertainty drives this adverse effect. Our results suggest that institutions should refrain from publishing such statements of concern
Keywords: C91; C72; L41; 330; beliefs; coordination device; strategic uncertainty; tacit collusion